STRATEGI SELF-BRANDING TIKTOK CELEBRITY DI KOTA MEDAN: ANALISIS ETNOGRAFI HIBRIDA PADA MICRO, MID-TIER, DAN MACRO - Kesia Vanessa Br Tarigan; Daud, Daud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research explores self-branding strategies of TikTok celebrities in Medan City and their interaction dynamics with audiences in forming digital self-image. The study employs a hybrid ethnography approach combining online and offline ethnographic practices. Informants consist of six TikTok celebrities (3 micro, 2 mid-tier, 1 macro) and active audience members. Data collection techniques include online observation, hybrid field interaction, interviews, visual documentation, and comment analysis. Findings indicate that TikTok celebrities do not initially construct an idealized image conceptually, but rather form it through audience response, engagement patterns, and platform algorithms. Successful self-branding emphasizes identity differentiation, content consistency, and performative acts. The constructed self-image influences not only digital popularity but also economic opportunities, social relations, and offline identity roles.